The Effectiveness of Upper Limb Offload Dynamic Taping Technique on Scapular Muscles Activation During Elevation in Healthy Subjects - Tian-zong Huang; Suhn-yeop Kim (Korean Research Society of Physical Therapy, 2020)
Background: For performing various movements well, cooperation between the muscles around the scapula and shoulder has been emphasized. Taping has been widely used clinically as a helpful adjunct to other physiotherapy methods for shoulder pathology and dysfunction treatment. Previous studies have evaluated the effect of taping techniques using dynamic tapes on shoulder function and pain. However, no study investigated the electromyographic (EMG) changes in the shoulder muscles. Objects: This study aimed to investigate the effect of the upper limb offload taping technique using a dynamic tape on EMG activities of the upper trapezius (UT), lower trapezius, serratus anterior (SA), and middle deltoid (MD) muscles during scaption plane elevation. Methods: A total of 26 healthy subjects (19.85 ± 6.40 years, male = 20) volunteered to participate in this study. The subjects were instructed to perform scaption elevation with and without dynamic taping on the shoulder. Shoulder elevation strength tests were performed at 100%, 75%, 50%, and 25%, for the maximal isometric contraction force. Results: There were statistically significant interaction effects between the taping application and shoulder scaption elevation force in EMG activities in the UT (p < 0.05) and MD (p < 0.05). EMG activities in the UT showed significant increases in 50%RVC (reference voluntary contraction, p < 0.05) and 25%RVC (p < 0.01). Furthermore, the EMG activity of the SA significantly increased in 50%RVC (p < 0.01) and 25%RVC (p < 0.01) after dynamic taping. For the MD, the EMG activity level significantly decreased in 100%RVC (p < 0.05). Conclusion: These results indicated that upper limb offload dynamic taping application affects the muscle activities of some shoulder muscles depending on different scaption elevation strength levels. Therefore, we suggest that the upper limb offload dynamic taping can be applied to the shoulders when patients need middle deltoid inhibition or upper trapezius facilitation, such as patients with shoulder impingement syndrome.